Tools for strengthening productive capacities in beekeepers from the Central Pacific Region of Costa Rica - Hernández-Ching, Paola (2023)
Ponencia presentar en el APIMONDIA : 48th Congreso Internacional de Apicultura ( 2023: setiembre 4-8 : Santiago, Chile)